Rigid-plastic analysis of floating ice sheets under impact loads - Kennedy, John B.; Iyengar, K. J. (Canadian Journal of Civil Engineering, 1981)
The deformation response of floating ice sheets under high intensity, short duration loads is examined. Using a rigid-plastic theory, together with a Tresca yield criterion, expressions are derived for the total time of response and the final deformed configuration of floating ice sheets. The influence of the magnitude of the impact load and the load-contact radius on the various design quantities such as deflection profile and stress distribution is discussed. Based on the results derived, a design method is presented to find the safe thickness of a floating ice sheet to sustain a given impact load. The method is illustrated with a numerical example.